ZINA, QADZAF, DAN MINUMAN KERAS DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Farihi, Hamid (IBN KHALDUN BOGOR, 2014)
Zina, Qadzaf, and Liquor in the Perspective of Islamic Criminal Law. The conception of Islam in particular concerning criminallaw, can basically be taken into consideration as well as input for the development of national laws in the future. Therefore, it would need to be pursued in earnest to provide input to the relevant parties, both government and legislative branches to work together to realize the national criminal law in accordance with the aspirations and expectations of the people.